2020
DOI: 10.1186/s13071-020-3909-6
|View full text |Cite
|
Sign up to set email alerts
|

Fowlerstefin, a cysteine protease inhibitor of Naegleria fowleri, induces inflammatory responses in BV-2 microglial cells in vitro

Abstract: Background: Naegleria fowleri is a free-living amoeba that causes an opportunistic fatal infection known as primary amoebic meningoencephalitis (PAM) in humans. Cysteine proteases produced by the amoeba may play critical roles in the pathogenesis of infection. In this study, a novel cysteine protease inhibitor of N. fowleri (fowlerstefin) was characterized to elucidate its biological function as an endogenous cysteine protease inhibitor of the parasite as well as a pathogenic molecule that induces immune respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…This includes proteins to facilitate the destruction of the mucus barrier, apoptosis of epithelial cells and re-arrangement of the host actin cytoskeleton to gain access to host tissue. In protozoan and sporozoite parasites cysteine proteases, such as cathepsin B identified in our study are critical for contact dependent host invasion through proteolysis of host extracellular matrix proteins and degradation of host immune proteins, including the amoeba genus Naegleria and E. histolytica (98,150,151). Cathepsin B expression in the parasite Giardia duodenalis, is induced by soluble host factors that deter attachment (105).…”
Section: Parasite Invasion and Contact Dependent Cysteine Proteasesmentioning
confidence: 69%
“…This includes proteins to facilitate the destruction of the mucus barrier, apoptosis of epithelial cells and re-arrangement of the host actin cytoskeleton to gain access to host tissue. In protozoan and sporozoite parasites cysteine proteases, such as cathepsin B identified in our study are critical for contact dependent host invasion through proteolysis of host extracellular matrix proteins and degradation of host immune proteins, including the amoeba genus Naegleria and E. histolytica (98,150,151). Cathepsin B expression in the parasite Giardia duodenalis, is induced by soluble host factors that deter attachment (105).…”
Section: Parasite Invasion and Contact Dependent Cysteine Proteasesmentioning
confidence: 69%
“…Studies have reported the essential role of parasitic protozoan cysteine protease inhibitors in the survival and infectivity of parasites in hosts by regulating endogenous or exogenous proteases [27][28][29][30]. Previously, we identified and characterized a novel stefin-family cysteine protease inhibitor of N. fowleri, known as fowlerstefin [13]. In this study, we characterized the second cysteine protease inhibitor of N. fowleri, NfCPI.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitory activity of NfCPI against cysteine proteases was determined by measuring the residual enzyme activity after incubation of each enzyme with NfCPI [12,13]. Cysteine proteases used in this study were papain (Sigma, St. Louis, MO, USA) and two recombinant cathepsin-B and cathepsin-B-like cysteine proteases of N. fowleri (NfCB and NfCBL).…”
Section: Inhibitory Activity Assaymentioning
confidence: 99%
See 2 more Smart Citations